The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1021/jacs.5b00786
|View full text |Cite
|
Sign up to set email alerts
|

A New Class of Non-C2-Symmetric Ligands for Oxidative and Redox-Neutral Palladium-Catalyzed Asymmetric Allylic Alkylations of 1,3-Diketones

Abstract: We report the discovery, synthesis, and application of a new class of non-C2-symmetric phosphoramidite ligands derived from pyroglutamic acid for use in both oxidative and redox-neutral palladium-catalyzed asymmetric allylic alkylations of 1,3-diketones. The resulting chiral products are typically obtained in high yield with good to excellent levels of enantioselectivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(38 citation statements)
references
References 81 publications
0
38
0
Order By: Relevance
“…Our approach herein was to examine non–C 2 -symmetric central chirality, and to investigate topologies not previously explored ( 106 ), with a particular focus on chiral 1,2-diamines and their derivative salens as chiral motifs with wide-ranging potential in asymmetric catalysis. Systems built around amino acid, terpenoid, and carbohydrate scaffolds were initially explored.…”
Section: Introductionmentioning
confidence: 99%
“…Our approach herein was to examine non–C 2 -symmetric central chirality, and to investigate topologies not previously explored ( 106 ), with a particular focus on chiral 1,2-diamines and their derivative salens as chiral motifs with wide-ranging potential in asymmetric catalysis. Systems built around amino acid, terpenoid, and carbohydrate scaffolds were initially explored.…”
Section: Introductionmentioning
confidence: 99%
“…Allylic functionalization provides a direct path to chiral synthons with a newly formed stereocenter from petrochemical feedstocks while preserving the olefin functionality as a handle for further elaboration. Various metal-based catalysts have been discovered for the enantioselective allylic C–H oxidation of simple alkenes with cyclic or terminal double bonds 816 . However, a general and selective allylic oxidation remains elusive with the more common internal alkenes.…”
mentioning
confidence: 99%
“…In recent years, we and others have reported that phosphoramidite ligands are compatible with Pd‐catalyzed allylic C−H functionalizations, some of which enable a diverse range of regio‐ and stereoselective allylic C−H alkylation reactions of 1,4‐dienes with various soft carbon nucleophiles (Scheme A). By means of DFT calculations, we identified that the geometry and coordination pattern of nucleophiles lead to different bond‐forming transition states and thereby determine the Z / E selectivites and regioselectivities (Scheme B) .…”
Section: Methodsmentioning
confidence: 99%